Orzecznictwo sygnalizacyjne Trybunału Konstytucyjnego w latach 2009–2013 - Kuczma, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
Signalling of loopholes and oversights in the law is one of the constitutional competences of the Constitutional Tribunal. However, it is evident that the signalling function of the Tribunal has incidental character compared to its remaining functions.The article analyses the signalling decisions of the Constitutional Tribunal issued in the period of 2009–2013. In the first part addressees of signal decisions were introduced along with the assessmentwhether the decisions were addressed at competent authorities. It turns out that in practice the addressee of a decision is not always the organ which prepared the legal document containing the errors. Deliberations in the following part of the paper concern the time within which the signalling decisions shall be issued. An attempt is made to answer the question whether it is precisely stipulated in the relevant provisions or can it be determined by way of interpretation. The next section refers to the reaction to the signalling decisions by their addressees. Finally, the issue of the significance of the signalling decisions has been brought up as well as the matters which inspired the Tribunal to exercise its signalling competence. At the end of the paper current practice is summarised and certain remarks de lege ferenda are formulated.
Keywords: Trybunał Konstytucyjny; orzecznictwo sygnalizacyjne